Визначення економічної ефективності заходів з поліпшення умов праці на підприємстві харчової промисловості - Євтушенко, Ольга Володимирівна; Сірик, Аліна Олегівна; Породько, Петро Вікторович (My University, 2015)
У статті на основі статистичних даних визначено економічну ефективності від впровадження автоматизованої системи управління охороною праці для підприємства харчової промисловості, за рахунокреалізації можливостей щодо прогнозування кількості днів непрацездатності від травматизму та професійних захворювань. Отримані результати можуть бути використані при вдосконаленні проектів управлінських рішень щодо забезпечення безпечних умов праці робітників підприємств харчової промисловості, а також підприємств інших галузей промисловості України. In the article, based on the statistics, economic effectiveness was defined as the implementation of the automated system management by occupational safety for the food industry enterprise due to the implementation of capacities to predict the amount of days of disability from injuries and occupational diseases. The research for the average meat-processing enterprise (slaughterhouse) of Ukraine was done, based on statistics of 2013 — 2014. Therefore was estimated: savings from reduction of occupational morbidity; savings due to the transfer of workers, payment of which was given at the rate of work in hazardous working conditions; damage to the company due to occupational diseases and injuries. The results can be used in improving projects of management decisions to ensure safe working conditions of the employees of the food industry enterprises as well as of enterprises of other industries of Ukraine
Keywords: кафедра екології та екоменеджменту; охорона праці; безпека; праця; виробничий травматизм; нещасний випадок; accident; occupational safety; safety; labour; occupational injuries